2018
DOI: 10.1007/s12040-018-1034-0
|View full text |Cite
|
Sign up to set email alerts
|

Geological, geochemical and Rb–Sr isotopic studies on tungsten mineralised Sewariya–Govindgarh granites of Delhi Fold Belt, Rajasthan, NW India

Abstract: Neoproterozoic granites are widespread in the Delhi Fold Belt of the Aravalli craton, some of which are associated with tungsten mineralisation. In one such instance, the volcano-sedimentary sequence of Barotiya Group in the South Delhi Fold Belt is intruded by a pluton of biotite granite gneiss known as Sewariya Granite (SG) and later by stocks and dyke swarm of tourmaline leucogranite known as Govindgarh Granite (GG). GG magmatism was associated with wolframite mineralisation in hydrothermal quartz veins occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…Association of slivers of basement gneisses (Tobisch et al, ) in this part of SDT supports the argument that the granulites were probably part of Sandmata terrane. Further, in the northern part, the SDT was intruded by several phases of granites such as circa 967 Ma old Sendra granite ( 87 Sr/ 86 Sr—Tobisch et al, ; U‐Pb TIMS—Pandit et al, ) and 860 Ma old Sewariya granite (Rb‐Sr magmatic cooling age; Sivasubramaniam et al, ). Both types show the imprint of pervasive deformational‐metamorphic fabric, suggesting a major tectonothermal event in the SDT could be much younger (≤860 Ma) than the age of Grenvillian orogeny.…”
Section: Discussionmentioning
confidence: 99%
“…Association of slivers of basement gneisses (Tobisch et al, ) in this part of SDT supports the argument that the granulites were probably part of Sandmata terrane. Further, in the northern part, the SDT was intruded by several phases of granites such as circa 967 Ma old Sendra granite ( 87 Sr/ 86 Sr—Tobisch et al, ; U‐Pb TIMS—Pandit et al, ) and 860 Ma old Sewariya granite (Rb‐Sr magmatic cooling age; Sivasubramaniam et al, ). Both types show the imprint of pervasive deformational‐metamorphic fabric, suggesting a major tectonothermal event in the SDT could be much younger (≤860 Ma) than the age of Grenvillian orogeny.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent highlands in these areas include ADFB, Deodar Ridge and Devikot High (Figure 12). Accordingly, The Pan-African orogeny-related rocks are poorly exposed in the western and northwestern part of India (Ashwal et al, 2013;Crawford, 1975;Islam et al, 1999;Rathore et al, 1999;Xu et al, 2022; 8a; see also Ghosh et al, 2021;Just et al, 2011;Sivasubramaniam et al, 2019;Vijay Anand et al, 2018). Other 650-1000 Ma ages of monazite grains match with the rocks listed in Kaur et al, 2021) of the ADFBs (Table 5).…”
Section: Possible Sources Of Himmatnagar Sandstonementioning
confidence: 77%
“…The numbered fields in the ternary Ca‐Fe tot ‐Mg plot represent different rock types: (1) Li‐rich granitoid pegmatites and aplites, (2) Li‐poor granitoids and associated pegmatites and aplites, (3) Ca‐rich metapelites, metapsammites and calc‐silicate rocks, (4) Ca‐poor metapelites, metapsammites and quartz‐tourmaline rocks, (5) Metacarbonates and (6) Metaultramafics. In addition, tourmaline compositions (green field) from Sewariya‐Govindgarh granites (Delhi Supergroup; Sivasubramaniam et al, 2019) and Balda‐Motiya granites (Delhi Supergroup; Ghosh et al, 2021) are shown for comparison, (b) The plot showing variation in rutile trace element concentrations on the source discrimination diagram (Nb vs. Cr; Triebold et al, 2012). As per the plot, detrital rutile grains originate from metapelitic source lithologies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…REE modelling of the Sewariya-Govindgarh pluton indicates partial melting in different crustal level for magma generation. Further, the Rb-Sr mineral isochron for the Govindgarh granite furnished an age of 860±7 Ma (Sivasubramaniam et al, 2019).…”
Section: Uranium Ree Nb Ta W Oresmentioning
confidence: 99%